Media, Misinformation, and Democracy: Evaluating the Impact of Social Media on Political Discourse (Al-Aasar, 2024)
In the digital age, social media has fundamentally transformed political discourse, information dissemination, and the process of public opinion formation. While social media platforms provide easier access to information and encourage public participation in political discussions, they also facilitate the rapid spread of misinformation and propaganda. The circulation of false or misleading information can negatively influence political decision-making, undermine public trust, and weaken the credibility of democratic institutions. This research article examines the impact of social media on political discourse, explores the causes behind the spread of misinformation, and analyzes its potential effects on democratic systems. The study highlights that although social media can enhance democratic engagement, the absence of effective regulation, media literacy, and transparency in information systems may allow these platforms to disrupt democratic processes.